Thin vibrators with arbitrary excitation and surface impedance - Nesterenko, M. V.; Katrich, V. A.; Dakhov, V. M.; Berdnik, S. L. (Видавництво Національного університету "Львівська політехніка", 2009)
The approximate analytical solution of the integral equation concerning the current in a thin straight vibrator with variable complex surface impedance has been obtained. The vibrator is located in unlimited space and is excited by the arbitrary field of impressed sources. For the case of vibrator’s excitation in the distinct from the centre point along its length the calculations have been carried out and the plots of electrodynamic characteristics of the vibrator, depending on the magnitude and the type of its surface impedance and location of the point of excitation, are presented.
Keywords: vibrator; arbitrary point of excitation; surface impedance; electrodynamic characteristics